2000
DOI: 10.1046/j.1365-2265.2000.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene start codon polymorphism (FokI) and bone mineral density in healthy male subjects

Abstract: The study shows that in this population of healthy men there is a weak association between lumbar spine bone mineral density and FokI restriction fragment length polymorphism at the translation initiation site of the vitamin D receptor gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…Data on fetal and infant life and childhood had previously been collected prospectively. Between October 1996 and December 1998, questionnaires on health and lifestyle were completed and study members attended for clinical examination [3][4][5][6][7][8][9][10][11]. Ethical approval for the study was obtained from the appropriate Local Research Ethics Committees and all participants gave their written consent.…”
Section: Methodsmentioning
confidence: 99%
“…Data on fetal and infant life and childhood had previously been collected prospectively. Between October 1996 and December 1998, questionnaires on health and lifestyle were completed and study members attended for clinical examination [3][4][5][6][7][8][9][10][11]. Ethical approval for the study was obtained from the appropriate Local Research Ethics Committees and all participants gave their written consent.…”
Section: Methodsmentioning
confidence: 99%
“…These polymorphisms of VDR may have different functions depending on their locations (Slattery 2007). The FokI polymorphism is located near the 5′-UTR region of the gene within the DNA-binding domain (Kanan et al 2000;Ingles et al 2001;Kim et al 2001;Chen et al 2002;Tworoger et al 2009). Studies have explored the associations between VDR polymorphisms and human cancers, including colorectal adenomas, prostate cancer, breast cancer, bladder cancer and melanoma (Kearney et al 1996;Deeb et al 2007;Slattery 2007;Ishihara et al 2008;Theodoratou et al 2008;Tang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant differences in ligand affinity, DNA binding, or transactivation activity have been found between these two VDR forms when studied independently (Laaksonen et al, 2004), in transient transfection assays with a vitamin D-responsive reporter gene, the shorter VDR variant displayed higher potency than the longer one (Gross et al, 1998). It has been hypothesized that a less active VDR could be associated with either an increased susceptibility to cancer risk or to a more aggressive form of the disease (Kanan et al, 2000). In this study, we found that the FokI polymorphisms of the VDR gene were closely associated with GBC risk, suggesting that this locus could be used as a molecular marker for GBC.…”
Section: Discussionmentioning
confidence: 99%